Fenomena living together perspektif maqasid al-syariah: Kajian literatur terhadap dampak pada hifzh al-nafs dan hifzh al-nasl - Komariyah, Aliyah Nur (Maliki Interdisciplinary Journal, 2025)
The trend of living together without marriage (cohabitation) is increasingly prevalent in the globalization era, particularly among the younger generation. This study analyzes the phenomenon from the perspective of Maqasid Al-Syariah, specifically its impact on Hifzh al-Nafs (protection of the soul) and Hifzh al-Nasl (protection of progeny). The method used is a literature study with a content analysis approach applied to relevant journals and scholarly works. The results indicate that cohabitation potentially threatens individuals' physical and psychological health, increasing the risk of sexually transmitted infections, mental disorders, and domestic violence. Furthermore, this practice obscures lineage clarity, neglects children's fundamental rights, and weakens the family foundation. It is concluded that cohabitation fundamentally contradicts the principles of Maqasid Al-Syariah. Therefore, systematic efforts such as education, strengthening religious values, and the socialization of laws with a maqasid perspective are necessary to prevent the widespread practice of cohabitation.